Playing rogues - David Matencio (Eludamos)
This article explores how video games, with no apparent connection to the literary rogue, still articulate Picaresque episodes and simulate Picaresque experiences through their intended gameplay and worldbuilding. These experiences are a specific expression of the combination of mechanics, narrative, and the agency of the player around a defined type of character, the rogue. They show how pervasive the influence of Picaresque Literature is, influencing design choices and informing key forms of being and acting in virtual worlds. This paper aims to define what a Picaresque experience in video games is and how it is possible to produce them. To achieve this, three video games will be analysed to show the different specific tools video games use to enable these experiences. The analyses will be supported by a theoretical framework based on existing bibliography about agency, videoludic narrative, mechanics, and Picaresque Literature with the objective of offering a comprehensive description of Picaresque experiences while also explaining them as a transmedia phenomenon that demonstrates the influence of Picaresque Literature in video games.